The Impact of Hyperkalemia on Mortality and Healthcare Resource Utilization Among Patients With Chronic Kidney Disease: A Matched Cohort Study in China - Zhang, Jiahui; He, Xiaoning; Wu, Jing (Frontiers in Public Health, 2022)
Objectives: This study aimed to estimate the impact of hyperkalemia on 1-year survival and all-cause healthcare resource utilization among patients with chronic kidney disease in China. Methods: Adult new-onset chronic kidney disease patients were identified between 2012 and 2016, among which the hyperkalemia and non-hyperkalemia cohorts were further selected and matched. Survival and all-cause healthcare resource utilization during a 12 month period were compared using Kaplan-Meier curves with log-rank test, Cox proportional hazard model, and Kaplan-Meier sample average method. Results: Among 1,003 pairs of patients (mean age 67.2 ± 14.3 years), the 1-year all-cause mortality was 5.39-times higher in the hyperkalemia cohort than the non-hyperkalemia cohort (hazard ratio=5.39, P<0.001). The mean costs and number of healthcare services among the hyperkalemia patients were significantly higher (P<0.05) in each follow-up month. An annual increase cost of ¥38,479 was observed in the hyperkalemia cohort, largely due to the sharp increase in inpatient costs during the first month after hyperkalemia events (¥22,204 vs. ¥1,032, P<0.001). Medication costs were the most important cost component for both cohorts (¥26,786 [45%] vs. ¥12,378[60%]). However, hyperkalemia patients spent more on non-medication treatment (¥13,410[23%] vs. ¥2,335[11%]) including nursing, monitoring, etc. Hyperkalemia patients had more annual inpatient admissions (1.9 vs. 0.7) and length of stays (28.6 vs. 8.7), while the number of outpatient visits (36.8 vs. 36.4) were similar. Conclusions: In Chinese chronic kidney disease patients, hyperkalemia is associated with substantially increased clinical and economic burdens that are driven by the short period following the hyperkalemia events, which strengthens calls for sufficient supervision and management of serum potassium.